Parlamentets natur Utviklingen av norsk miljø- og petroleumspolitikk (1945-2013) - Gisle Andersen (Scandinavian University Press (Universitetsforlaget), 2017)
Sociology as a discipline is concerned with relationships. The relationship addressed in this book, is the one between society and nature. More specifically, the process of making pollution and the environmental condition relevant for - and in - parliament is used as an analytical prism to gain better understanding of that relationship. Building on theoretical perspectives from pragmatic moral-political sociology developed by Boltanski and Thévenot, the changing valuation of «nature» and «the environment» in Norwegian parliamentary debates is analysed: When and how is nature made a relevant for parliament? How is nature valued in these debates? How are decisions on environmental- and petroleum policy legitimated? What kind of knowledge is made relevant? In what ways have parliamentary debates changed over time and how can we understand these changes? Empirical data is an extensive sample of Norwegian parliamentary debates in the period 1945-2013. The book maps the historical trajectory of the political conflicts on the environmental consequences from industry in Norway, and the petroleum industry in particular. The analysis exposes how the form of valuable nature has changed substantially over time. That is, what makes nature valuable for parliament has changed over time. The changing form of valuable nature also has consequences for how pollution should be avoided and what kind of policy instruments that are considered relevant. In the early 20th century nature was primarily regarded as a robust and unchangeable entity. Starting from the early 1950s this understanding of nature is undergoing impor- 10 GISLE ANDERSEN | PARLAMENTETS NATUR tant changes. Rather than being viewed as a robust entity, nature is to larger extent seen as fragile and should be protected from humans: Nature should be conserved. During the next decades the relevant form of nature to protect is gradually redefined as «the environment». In contrast to the idea of protecting «nature» from humans, pollution was primarily a problem because it harmed the human environment. A significant change occurred during the 1990s. The Norwegian parliamentary debates from this period are characterised by a harsh ecological self-critique. This had several consequences, among them a new environmental statute in the Norwegian Constitution. A new way of valuing nature emerged: What is valued is not nature «itself» but the function that nature has for humans, the conservation of nature understood as a «life supporting production system» for humanity. This view of nature specified the valuation of nature as anthropocentric. Another important dimension of the new way of valuing nature is that it clearly limited what form of nature that should be protected: It is legitimate to pollute and to harm parts of nature, but only as long as one does not threaten the production system that humans depend upon. As long as an activity can go on without diminishing the functional utility of nature for humanity; use, change and destruction of nature can be considered legitimate. This could be understood as a minimum definition of sustainability. These changes are linked to the ways the modern societies today responds to, and tries to control, global environmental change.